Growth hormone secretagogue receptor‐1a mediates ghrelin's effects on attenuating tumour‐induced loss of muscle strength but not muscle mass. Issue 5 (15th July 2021) - Liu, Haiming; Zang, Pu; Lee, Ian (In‐gi); Anderson, Barbara; Christiani, Anthony; Strait‐Bodey, Lena; Breckheimer, Beatrice A.; Storie, Mackenzie; Tewnion, Alison; Krumm, Kora; Li, Theresa; Irwin, Brynn; et al.
Abstract: Background: Ghrelin may ameliorate cancer cachexia (CC) by preventing anorexia, muscle, and fat loss. However, the mechanisms mediating these effects are not fully understood. This study characterizes the pathways involved in muscle mass and strength loss in the Lewis lung carcinoma (LLC)‐induced cachexia model, and the effects of ghrelin in mice with or without its only known receptor: the growth hormone secretagogue receptor‐1a ((GHSR‐1a), Ghsr +/+ and Ghsr −/− ). Methods: Five to 7‐month‐old male C57BL/6J Ghsr +/+ and Ghsr −/− mice were inoculated with 1 × 10 6 heat‐killed (HK) or live LLC cells (tumour implantation, TI). When tumours were palpable (7 days after TI), tumour‐bearing mice were injected with vehicle (T + V) or ghrelin twice/day for 14 days (T + G, 0.8 mg/kg), while HK‐treated mice were given vehicle (HK + V). Body weight and grip strength were evaluated before TI and at termination (21 days after TI). Hindlimb muscles were collected for analysis. Results: Less pronounced body weight (BW) loss (87.70 ± 0.98% vs. 83.92 ± 1.23%, percentage of baseline BW in tumour‐bearing Ghsr +/+ vs. Ghsr −/−, P  = 0.008), and lower upregulation of ubiquitin‐proteasome system (UPS, MuRF1/ Trim63, 5.71 ± 1.53‐fold vs. 9.22 ± 1.94‐fold‐change from Ghsr +/+ HK + V in tumour‐bearing Ghsr +/+ vs. Ghsr ‐/‐, P  = 0.036) and autophagy markers ( Becn1, Atg5, Atg7, tumour‐bearing Ghsr +/+  <  Ghsr −/−, all P  < 0.02) were found in T + V Ghsr +/+ vs. Ghsr −/− mice. Ghrelin attenuated LLC‐induced UPS marker upregulation in both genotypes, [ Trim63 was decreased from 5.71 ± 1.53‐fold to 1.96 ± 0.47‐fold in Ghsr +/+ (T + V vs. T + G: P  = 0.032) and 9.22 ± 1.94‐fold to 4.72 ± 1.06‐fold in Ghsr −/− (T + V vs. T + G: P  = 0.008)]. Only in Ghsr +/+ mice ghrelin ameliorated LLC‐induced grip strength loss [improved from 89.24 ± 3.48% to 97.80 ± 2.31% of baseline (T + V vs. T + G: P  = 0.042)], mitophagy markers [ Bnip3 was decreased from 2.28 ± 0.56 to 1.38 ± 0.14‐fold (T + V vs. T + G: P  ≤ 0.05)], and impaired mitochondrial respiration [State 3u improved from 698.23 ± 73.96 to 934.37 ± 95.21 pmol/min (T + V vs. T + G: P  ≤ 0.05)], whereas these markers were not improved by ghrelin Ghsr −/− . Compared with Ghsr +/+, Ghsr −/− tumour‐bearing mice also showed decreased response to ghrelin in BW [T + G‐treated Ghsr +/+ vs. Ghsr −/− : 91.75 ± 1.05% vs. 86.18 ± 1.13% of baseline BW, P  < 0.001)], gastrocnemius (T + G‐treated Ghsr +/+ vs. Ghsr −/− : 96.9 ± 2.08% vs. 88.15 ± 1.78% of Ghsr +/+ HK + V, P  < 0.001) and quadriceps muscle mass (T + G‐treated Ghsr +/+ vs. Ghsr −/− : 96.12 ± 2.31% vs. 88.36 ± 1.94% of Ghsr +/+ HK + V, P  = 0.01), and gastrocnemius type IIA (T + G‐treated Ghsr +/+ vs. Ghsr −/− : 1250.49 ± 31.72 vs. 1017.62 ± 70.99 μm 2, P  = 0.027) and IIB fibre cross‐sectional area (T + G‐treated Ghsr +/+ vs. Ghsr −/− : 2496.48 ± 116.88 vs. 2183.04 ± 103.43 μm 2, P  = 0.024). Conclusions: Growth hormone secretagogue receptor‐1a mediates ghrelin's effects on attenuating LLC‐induced weakness but not muscle mass loss by modulating the autophagy‐lysosome pathway, mitophagy, and mitochondrial respiration.